On a collection of spiders (Arachnida: Araneae) from the island of Seili, with a new record for the Finnish fauna and a list of species from the island - Zamani Alireza; Österman Emil M.; Koponen Seppo (Arachnologische Ges., 2025)
The results of a recent collection effort on the island of Seili (located in the Archipelago Sea, off the southwest coast of Finland in the Baltic Sea, Swedish name Själö) are reported herein. Out of 709 specimens collected at two sites using four different collection methods, 173 were adults (26 males, 147 females) and identifiable to species-level, resulting in 33 species from 13 families, including five species newly reported from the island. A male of Cheiracanthium punctorium (Villers, 1789), separately collected at a different place, represents the first record of this species in Finland and its northernmost record across its whole known range. An updated list of spider species reported from Seili (215 species from 25 families) is included as an appendix.